2005
DOI: 10.1016/j.amjhyper.2004.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary salt loading on the responses of isolated rat mesenteric arteries to leptin

Abstract: These results indicate that salt loading to rats almost completely abolishes the vasodilatation to leptin. This implies endothelial disruption and, unlike the response to acetylcholine, no other vasodilator mechanism is implicated. This could provide a link between high salt intake and hypertension because the known increase in sympathetic activity caused by leptin would not be countered by a direct vasorelaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
9
2
Order By: Relevance
“…However, in the setting of obesity, metabolic syndrome and type 2 diabetes -conditions associated with chronic hyperleptinemia -acute depressor effects of leptin are impaired leading to the unbalanced SNS activation and BP elevation (Martin et al 2008). Impairment of the vasodilatory effect of leptin was also observed in rats fed high-salt diet (Jaffar et al 2005) and in spontaneously hypertensive rat (Rodríguez et al 2006). Elucidating the mechanisms of this "vascular leptin resistance" may help in developing novel therapies for arterial hypertension associated with the metabolic syndrome, one of the most common forms of hypertension nowadays.…”
Section: Introductionmentioning
confidence: 94%
“…However, in the setting of obesity, metabolic syndrome and type 2 diabetes -conditions associated with chronic hyperleptinemia -acute depressor effects of leptin are impaired leading to the unbalanced SNS activation and BP elevation (Martin et al 2008). Impairment of the vasodilatory effect of leptin was also observed in rats fed high-salt diet (Jaffar et al 2005) and in spontaneously hypertensive rat (Rodríguez et al 2006). Elucidating the mechanisms of this "vascular leptin resistance" may help in developing novel therapies for arterial hypertension associated with the metabolic syndrome, one of the most common forms of hypertension nowadays.…”
Section: Introductionmentioning
confidence: 94%
“…Jaffar et al. 46 have shown that leptin induces less marked endothelium‐dependent NO‐mediated relaxation of mesenteric arteries in rats fed a high‐salt diet. Similarly, the ability of leptin to inhibit angiotensin II‐induced contraction of aortic rings is less marked in spontaneously hypertensive rats (SHR) than in normotensive animals 47 .…”
Section: Resistance To the Vascular No‐mimetic Effect Of Leptinmentioning
confidence: 99%
“…Nevertheless, subthreshold concentrations of insulin augment the effect of leptin on Akt phosphorylation, eNOS phosphorylation and NO release [33]. Recently, it was demonstrated that feeding rats a highsalt diet for 1 month attenuates the vasodilatory NOdependent effect of leptin on isolated mesenteric arteries [34].…”
Section: Leptin and Nitric Oxidementioning
confidence: 99%